Gestión de inventarios en la hacienda bananera la unión de la Empresa Reybanpac ubicada en el Cantón Puebloviejo parroquia san juan periodo 2022. - Espinoza Álvarez, Geoconda Roció (2023)
The present research work frames the inventory management control within the Reybanpac Company located in Puebloviejo parish San Juan in the period 2022, it is dedicated to the production, marketing and export of bananas; the objective of this study focuses on analyzing and proposing inventory management strategies that allow cost reduction and efficient improvement of the agricultural company Reybanpac. Currently, managing an adequate inventory control process is based on planning, coordinating and controlling the company's merchandise or product inputs and outputs, in order to have adequate levels of products at the right time and in the right place. Good inventory management results in multiple benefits for Reybanpac, while poor inventory management can lead to unnecessary costs and excess inventories. One of the most efficient alternatives in inventory management control is based on inventory turnover, which implies the elimination of obsolete or unsold products versus the optimization of the levels of products sold, in order to maximize the profitability of inventories and thus avoid the cost of storage and handling of products that do not generate sales. Finally, this study will implement the use of different types of research techniques and tools that will be applied to determine the profitability and future success of the company.